2012
DOI: 10.1615/intjmedmushr.v14.i5.10
|View full text |Cite
|
Sign up to set email alerts
|

Neuroregenerative Potential of Lion's Mane Mushroom, Hericium erinaceus (Bull.: Fr.) Pers. (Higher Basidiomycetes), in the Treatment of Peripheral Nerve Injury (Review)

Abstract: We present a model case study of the activity of aqueous extract of Hericium erinaceus fresh fruit bodies in promoting functional recovery following crush injury to the peroneal nerve in adult female Sprague-Dawley rats. The aim was to explore the possible use of this mushroom in nerve repair. The activities of aqueous extract were compared to activities exhibited by mecobalamin (vitamin B12), which has been widely used in the treatment of peripheral nerve disorders. Analysis of walking track indicated that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 62 publications
0
26
0
1
Order By: Relevance
“…The fruiting body of H. erinaceus is commercially cultivated and has attracted increasing attention in pharmaceutical and functional food industries because of its health promotion and disease alleviation effects on human health. 1,2 Thus, pills containing the dried fruiting body of H. erinaceus are manufactured and used as a health food.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The fruiting body of H. erinaceus is commercially cultivated and has attracted increasing attention in pharmaceutical and functional food industries because of its health promotion and disease alleviation effects on human health. 1,2 Thus, pills containing the dried fruiting body of H. erinaceus are manufactured and used as a health food.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Upregulation of signaling pathways as well as axonal protein synthesis and degradation are consistent with the beginning of motor functional recovery of injured limb (Wong et al, 2009a(Wong et al, , 2011(Wong et al, , 2012. It has been shown that cultivation conditions did not affect selected bioactive properties of H. erinaceus grown in tropical Malaysia (Wong et al, 2009b).…”
Section: Introductionmentioning
confidence: 87%
“…Further, scientific validation of traditional knowledge bears evidence of the many positive effects of consuming mushrooms fresh or processed on human health. A wide variety of bioactive compounds isolated from many species of mushrooms have been identified [9].…”
Section: Introductionmentioning
confidence: 99%